Depression in seniors vs. their nutritional status and nutritional knowledge - Wojciak, Rafal Wojciech; Mojs, Ewa; Staniek, Halina; Marcinek, Katarzyna; Krol, Ewelina; Suliburska, Joanna; Krejpcio, Zbigniew (Journal of Medical Science, 2016)
Aim. There is a limited amount of data on depression in elderly people and even less is known about the relationship between nutritional status and nutritional habits, and mood disorders in this group. The foregoing paper investigates this relationship and evaluates the family status of seniors with depression. Material and methods. The research was conducted on a group of 85 seniors in the ages of 60–91 years. The depression symptoms, nutritional knowledge and nutritional status were investigated and their relationship in elderly women. Results. Depression was present in 27% of women. Seniors with depression had a significantly lower BMI and a larger number of them had better nutritional knowledge than the rest of women. Women with the lowest BMI were statistically younger, had better nutritional knowledge and higher level of depression than women with normal BMI. There is a relationship between depression and family status of seniors. A significantly larger number of single women suffered from depression (50%) in comparison with women in relationships (25%) and single widows (23%). Conclusions. Research showed that there is a relationship between symptoms of depression in elderly women with nutrition and family status. Extending research in order to evaluate nutrition disorders in seniors, which influence their mood disorders seems justified.